1974
DOI: 10.1136/jnnp.37.10.1105
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial volume-pressure relationships during experimental brain compression in primates: 3. Effect of mannitol and hyperventilation

Abstract: SY N OP SI S In 10 anaesthetized and ventilated baboons a steady level of raised intracranial pressure was achieved by graduated inflation of an extradural balloon. Measurements were made of the ventricular fluid pressure, and of the change in this pressure after injection of 0 05 ml into the ventricle, the volume-pressure response. This response was studied at normocapnia and at hypocapnia (induced by hyperventilation), and before and after the intravenous administration of mannitol under normocapnic and hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…This interesting phenomenon has been noted previously by one of the authors. Lofgren (1974) has also shown that increases in arterial carbon dioxide tension, which produce cerebral arteriolar dilatation, do not affect the elastance, and this has been confirmed by the present authors (Leech and Miller, 1974b) using the different method of measuring elastance already described. These findings tend to argue against the theory that arterial pressure increases elastance during venous compression because of a rise in mean intravascular pressure, since CO2 will also increase mean intravascular pressure during venous compression by reducing arterial/ arteriolar resistance and permitting the head of pressure to be transferred downstream.…”
Section: Experimental Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…This interesting phenomenon has been noted previously by one of the authors. Lofgren (1974) has also shown that increases in arterial carbon dioxide tension, which produce cerebral arteriolar dilatation, do not affect the elastance, and this has been confirmed by the present authors (Leech and Miller, 1974b) using the different method of measuring elastance already described. These findings tend to argue against the theory that arterial pressure increases elastance during venous compression because of a rise in mean intravascular pressure, since CO2 will also increase mean intravascular pressure during venous compression by reducing arterial/ arteriolar resistance and permitting the head of pressure to be transferred downstream.…”
Section: Experimental Methodssupporting
confidence: 86%
“…This interesting phenomenon has been noted previously by one of the authors. Lofgren (1974) has also shown that increases in arterial carbon dioxide tension, which produce cerebral arteriolar dilatation, do not affect the elastance, and this has been confirmed by the present authors (Leech and Miller, 1974b) In any patient with raised intracranial pressure, the occurrence of arterial hypertension, whether spontaneous or therapeutically induced, will lead to a pronounced increase in brain elastance. This implies that any increase in intracranial volume will then result in a large rise in intracranial pressure.…”
Section: Discussionsupporting
confidence: 73%
“…I n brain tumours a restoration of the autoregulation after steroids has been described ( REULEN et al 1972 . In postischaemic periods and during ICP increase, arterial hypertension will have a deleterious effect, and may provoke brain oedema (LEECH & MILLER 1974, FENSKE et al 1975.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the intracranial volume-pressure relationship for understanding the pathophysiology of raised ICP and ICPPA has been demonstrated in several studies [4,27,28,30,32,43,49,51].…”
Section: Icp Pulse Amplitudementioning
confidence: 99%